[P135] Should there be more optimization of cone beam ct imaging used with image guided radiotherapy. (August 2018) - Martin, Colin; Abuhaimed, Abdullah
Abstract : Purpose: Cone beam CT (CBCT) is used in improving delivery of image guided radiation therapy (IGRT). However, less attention is paid to optimization of imaging for individual patients than in diagnostic applications. Methods are required to evaluate patient doses resulting from imaging procedures in order to facilitate optimization. Methods: A modified version of the CT dose index (CTDI) has been proposed by the International Electrotechnical Commission (CTDIIEC) based on measurements with longer CTDI chambers. A dose–width product can be calculated by multiplying the CTDIIEC by the width of the CBCT beam and this is proposed as a quantity that can be used for dose assessment and linked to effective dose for optimization. Monte Carlo simulations based on a Varian On Board Imaging (OBI) system have been used to derive conversion coefficients that enable organ doses and effective dose for ICRP reference phantoms to be determined from the CTDIIEC for different scan protocols. Results: Coefficients to allow estimation of effective doses for reference phantoms from the dose-width product have been derived for head (0.0034 mSv(mGy cm) −1 ), thorax (0.0252 mSv(mGy cm) −1 ) abdomen, (0.0216 mSv(mGy cm) −1 ) and pelvis (0.0150 mSv(mGy cm) −1 ) protocols. These can be helpful in assessing overall optimization of the imaging process. However, organ doses are required for optimization of procedures for individual patients. Since standard exposure factors and field sizes are used frequently for CBCT, more organs are irradiated and dose levels are proportionately higher for smaller patients, than they are in diagnostic procedures. Conclusions: Data on effective doses from CBCT imaging can be used in making judgements on the contributions to patient dose from imaging, and thereby assist in optimization of IGRT regimes. More attention is required in selection of exposure factors and field sizes for CBCT used with IGRT.